A combined single crystal neutron/X-ray diffraction and solid-state nuclear magnetic resonance study of the hybrid perovskites CH3NH3PbX3 (X = I, Br and Cl)1. Issue 17 (7th May 2015) - Baikie, Tom; Barrow, Nathan S.; Fang, Yanan; Keenan, Philip J.; Slater, Peter R.; Piltz, Ross O.; Gutmann, Matthias; Mhaisalkar, Subodh G.; White, Tim J.
<x xml:space="preserve">Abstract</x> This article describes a variable temperature solid-state NMR and single crystal X-ray/neutron diffraction study of the hybrid perovskites (CH3NH3)PbX3 (X = I, Br and Cl).